New approach to accurate interpretation of sickle cell disease newborn screening by applying multiple of median cutoffs and ratios. Issue 9 (21st May 2018) - Allaf, Bichr; Patin, Franck; Elion, Jacques; Couque, Nathalie
Abstract: Background: The main goal of newborn screening (NBS) for sickle cell disease (SCD) is to detect affected neonates so that specific preventive care can be implemented. High‐performance liquid chromatography (HPLC) used for NBS has high sensitivity and specificity, but we lack guidelines for quantitative hemoglobin (Hb) fraction interpretation. The purpose of this study was to determine cutoff values to standardize quantitative interpretation in SCD NBS for different clinical situation such as, red blood cell transfusion or beta‐thalassemia, which can be real screening pitfalls. Methods: Retrospective study of 75, 026 samples from the neonatal screening program analyzed in our laboratory. Precise HbA and HbS percentages at birth were recorded and median values established for each gestational age, allowing percentage results to be expressed in normal gestation‐specific multiples of the median (MoM). Three threshold values of clinical interest were determined. Results: High levels of HbA (>2.5 MoM) allowed identification of newborns who received transfusions. Low levels of HbS (≤0.7 MoM) allowed detection of the association between HbS and other mutations of the beta‐globin gene (i.e., HbHope, β0‐thalassemia, etc.). An HbA/HbS ratio <0.5 to distinguish healthy carriers from SCD with S/β+‐thalassemia. The screening accuracy for each threshold was established. The screening accuracy of low‐level HbA, which is determinant in identifying the subgroup of patients at risk of β‐thalassemia, will be determined prospectively. Conclusions: This new approach introduces tools for a quantitative interpretation in SCD NBS by HPLC methods and could allow standardization of interpretation between centers.